Nucleation and epitaxial growth of Ge nanoislands on Si surface prepatterned by ion irradiation. Issue 8 (5th July 2013) - Smagina, Zhanna; Novikov, Pavel; Zinovyev, Vladimir; Stepina, Natalya; Dvurechenskii, Anatoly; Armbrister, Vladislav; Seleznev, Vladimir; Kuchinskaya, Polina
<x xml:space="preserve">Abstract</x> Experimental study of Ge nanoislands growth on groove‐patterned Si(001) substrate formed by ion‐beam‐assisted nanoimprint lithography is carried out. Prepatterning procedure includes ion irradiation of Si substrate through imprinted resist mask and subsequent selective etching of irradiated Si domains. It is shown that temperature during ion irradiation affects the location of subsequently grown Ge nanoislands. The effect is interpreted in terms of additional surface tensile strain formed inside grooves by residual irradiation‐induced defects. The effect is stronger for cold irradiated samples due to higher density of residual defects.